Features of developing SARS-CoV-2 nucleocapsid protein population-based seroprevalence during the first wave of the COVID-19 epidemic in the Russian Federation - Popova, A. Yu; Andreeva, E. E.; Babura, E. A.; Balakhonov, S. V.; Bashketova, N. S.; Bulanov, M. V.; Valeullina, N. N.; Goryaev, D. V.; Detkovskaya, N. N.; Ezhlova, E. B.; Zaitseva, N. N.; Istorik, O. A.; et al. (Infekt͡s︡ii͡a︡ i immunitet, 2021)
The novel coronavirus (SARS-CoV-2) pandemic, dubbed COVID-19, has become one of the most serious challenges for human populations in the vast majority of countries worldwide. Rapid spreading and increased mortality related to it required new approaches to manage epidemic processes on a global scale. One of such approaches was based on analyzing SARS-CoV-2 seroprevalence associated with COVID-19. Our aim was to summarize the results on assessing seroprevalence to the SARS-CoV-2 nucleocapsid antigen (Nc) in residents from 26 regions of the Russian Federation, carried out during the first wave of the COVID-19 epidemic.Materials and methods. Seroprevalence distribution was examined in 26 model regions of the Russian Federation according to the unified method developed by the Rospotrebnadzor with the participation of the Federal State Institution Saint Petersburg Pasteur Research Institute of Epidemiology and Microbiology. Such approach implied formation of a group of volunteer subjects in model geographic region who were tested by ELISA for anti-Nc serum antibody level in peripheral blood. Analyzed primary data obtained in separate regions were either accepted for publication or released.Results. The current paper finalizes the data obtained in all 26 regions of the Russian Federation. The total SARS-CoV-2 seroprevalence was 19.5 (10.0–25.6)% with the maximum and minimum value found in the Kaliningrad Region and the Republic of Crimea, respectively (50.2% vs. 4.3%). A pattern of age-related seroprevalence distribution indicates insignificant predominance of seroprevalence among subjects of 1–17 years old: 22.1 (13.1–31.8)%. Among COVID-19 convalescents positive for SARS-CoV Nc antibodies it reached 60.0 (40.0–73.3)%. The number of contact persons comprised 6285 subjects or 8.5% of total volunteer cohort, with the level of seroprevalence reaching up to 25.3 (17.95–35.8)%. A direct correlation was revealed between levels of seroprevalence in convalescent and contact volunteers. In addition, the reproductive number for SARS-CoV was calculated comprising 5.8 (4.3–8.5) suggesting that one convalescent subject can infect at least 4 healthy individuals. A high level of asymptomatic forms of COVID-19 among seropositive subjects was confirmed empirically comprising up to 93.6 (87.1–94.9)%.Conclusion. A single cross-sectional study performed during 2020 June–August timeframe allowed to assess pattern of sex- and agerelated COVID-19 seroprevalence for general population in 26 Russian Federation regions. The data obtained may serve as a basis for the longitudinal cohort investigation with serial subject sampling. The timing and duration of study will be determined by dynamics of ongoing COVID-19 epidemic.